2012
DOI: 10.1371/journal.pone.0037734
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Attention in Ambiguous Reversals of Structure-From-Motion

Abstract: Multiple dots moving independently back and forth on a flat screen induce a compelling illusion of a sphere rotating in depth (structure-from-motion). If all dots simultaneously reverse their direction of motion, two perceptual outcomes are possible: either the illusory rotation reverses as well (and the illusory depth of each dot is maintained), or the illusory rotation is maintained (but the illusory depth of each dot reverses). We investigated the role of attention in these ambiguous reversals. Greater avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 49 publications
1
21
1
1
Order By: Relevance
“…By comparison, object rotation is far more "flexible" in that reversals of apparent rotation are readily prompted by stimulus transients Stonkute, Braun, & Pastukhov, 2012). Accordingly, object shape may be treated as an invariant and may carry particular weight in determining the continuity and persistence of objects.…”
Section: Related Forms Of Sensory Memorymentioning
confidence: 99%
“…By comparison, object rotation is far more "flexible" in that reversals of apparent rotation are readily prompted by stimulus transients Stonkute, Braun, & Pastukhov, 2012). Accordingly, object shape may be treated as an invariant and may carry particular weight in determining the continuity and persistence of objects.…”
Section: Related Forms Of Sensory Memorymentioning
confidence: 99%
“…have recently shown that even when dealing with the ambiguous illusory states, the visual system takes into account the ecological plausibility of transitions between them. During the forced ambiguous switch, a reversal of the illusory rotation is preferred over the inversion of the illusory depth (this is true only when the object is not depth symmetric, as in the present experiment; for further details, please refer to Stonkute et al, 2012). However, these transformation constraints are unlikely to be relevant if there are interruptions in the perception of the illusory object.…”
Section: Resultsmentioning
confidence: 54%
“…Earlier work on SFM displays showed that the stability of perception depends primarily on the constancy of the interpolated illusory object (the surface interpolation hypothesis; Treue et al, 1995). Even large changes to the motion and location of individual dots, such as limiting their lifetimes (Brouwer & van Ee, 2006) or reversing their physical motions (Li & Kingdom, 1999;Petersik & Dannemiller, 2004;Stonkute et al, 2012;Zivotofsky & Goldstein, 2007), may not destabilize perception as long as the illusory shape remains the same.…”
Section: ) Nonmotion Dot Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we reanalyzed the data of (Stonkute, Braun, & Pastukhov, 2012), where attention was distracted in every trial by a concurrent task at the time of the sudden change in the planar motion of an SFM display (see Fig. 6A and Stonkute et al (2012) for details).…”
Section: Transformation Priming Cannot Be Explained By Selective Attementioning
confidence: 99%